Cortical anastomotic veins occlusion in the rat including the assessment of cerebral swelling - Cokluk, Cengiz; Aydin, Keramettin; Yemisci, Muge; Colakoglu, Serdar; Kaplan, Suleyman (Elsevier, 2006)
A rat model composed of the sacrifice of the anterior and posterior cortical anastomotic veins by microsurgical techniques was used for the assessment of brain swelling. Twenty male, 15-week-old Sprague-Dawley rats were used in this animal experiment. Small burr-holes were made over the anterior (the intersection of the line drawn from the posterior border of the orbital rim and the line drawn along the para-midline to the superior sagittal suture) and posterior (inferior point of the posterior end of the zygomatic arch) anastomotic veins. After performing a final inspection and describing the venous vessels, they were sacrificed using bipolar coagulation technique and micro-scissors. Specimens were evaluated using histopathological approach, albumin immunostaining technique and a stereological method. Hemispheric swelling, midline shift, brain oedema, subcortical petechial haemorrhagia, ischemia and necrosis were histopathological findings observed in this experimental study. The albumin immumostaining study demonstrated disrupted areas of the blood-brain barrier in the operated hemisphere. Stereological volumetric analysis revealed an 8% brain swelling in the operated hemispheres compared with unoperated ones. Our results suggest that the sacrifice of the anterior and posterior anastomotic veins may be used as an experimental rat model in the evaluation of brain damage and swelling caused by the occlusion of the venous anastomotic outflow. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: cerebral vein; anterior-posterior anastomotic veins; venous infarct; rat model; stereology